The Role of Diet Compared to Physical Activity on Women's Cancer Mortality: Results From the Third National Health and Nutrition Examination Survey - Chan, Joshua E.; Caesar, Michelle Ann; Mann, Amandeep K.; Koh-Bell, Alex; Richardson, Michael T.; Johnson, Caitlin R.; Kapp, Daniel S.; Chan, John K. (Frontiers in Public Health, 2022)
Background: Cancer is the second leading cause of death in women. Prior studies have examined how lifestyle factors, such as diet and physical activity, influence cancer mortality. However, few have evaluated if diet or physical activity has a stronger protective effect for cancer mortality. Therefore, this study aims to evaluate and compare the impacts of diet and physical activity on women’s cancer mortality. Methods: Prospective, cross-sectional data were abstracted from the Third US National Health and Nutrition Examination Survey (NHANES III) on female respondents from 1988-1994. Physical activity was derived from the CDC’s metabolic equivalent (MET) intensity levels. Dietary classifications were derived from the USDA’s healthy eating index (HEI). We utilized the National Death Index to obtain mortality follow-up information on our cohort until December 31, 2015. Chi-squared, multivariable Cox regression, and Kaplan-Meier estimates were employed for statistical analyses. Results: Of 3,590 women (median age: 57, range: 40-89), 30% had an obese BMI (BMI≥30 kg/m2). Additionally, 22% of participants self-reported a healthy diet, 69% needed dietary improvement, and 9% had a poor diet. Furthermore, 21% reported physical inactivity, 44% did not meet physical activity guidelines, and 35% met guidelines. On multivariate analysis, healthy diet (HR:0.70; 95% CI: 0.50-0.97; p=0.03), but not physical activity (HR: 0.91; 95% CI: 0.59-1.42; p=0.68), independently predicted for lower cancer mortality. Participants with a healthy diet but low exercise had decreased cancer mortality compared to participants with an unhealthy diet but high exercise (p=0.01).